Comparative study on the milk production at goats autochthonous breeds - Rodica Chetroiu; Ion Călin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The paper presents the research results on milk production, conducted in the goat farm of S.C. AGROFAM HOLDING Feteðsti, at the two autochthonous breeds: Alba de Banat and Carpatina, for a period of 3 years, between 2012 - 2014. Thus, the productive levels of the two breeds show very significant statistic differences, Alba de Banat breed being upper than Carpatina with 40.94 to 46.05%. Also, there are productive differences between lactations, the highest milk production being obtained in lactation 3 of each year under study, with an upward trend from the first lactation. After the 3rd lactation, milk production declines, being near the amount of the first lactation. During the period under study, the average farm yields of the both breeds fall on downward curves, due both to the shifting from mechanical milking to manual milking and to decreasing of the lactation duration. Practicing the mechanical milking is a technological factor of prime importance both in terms of achieving increased milk production and for producing a hygienic product and switching from mechanical milking to manual milking is a factor of production decrease, affecting the economic results of the farm.
Keywords: 330; milk; goats; lactations; breeds